Strategi Pengembangan Usaha Industry Kerajinan Rotan (Studi Kasus) Di Desa Keude Being Kecamatan Lhoknga Kabupaten Aceh Besar - Samsul Bahri; Teuku Makmur; Otto Nur Abdullah (Fakultas Pertanian, Universitas Syiah Kuala, 2021)
The rattan handicraft industry in Keude Bieng Village has produced various kinds of rattan handicraft products such as chairs, flower pots, trash cans, and serving hoods so that they can be comfortable and have their own charm compared to other rattan products. This study aims to determine what internal factors and external factors influence the strategy of developing rattan handicraft business in Keude Bieng Village, Lhoknga District, Aceh Besar District, and to determine the strategy of developing rattan handicraft business in Keude Bieng Village, Lhoknga District, Aceh Besar District. . The object of this research is focused on the strategy of developing the rattan handicraft industry in Keude Bieng Village and the scope of the research is limited to the strategy of developing the rattan handicraft industry in Keude Bieng Village, Lhoknga District, Aceh Besar District. The method used in this research is a case study. The results showed that the internal factors that could support the development of the rattan craft business in Keudee Bieng Village were the strength factor which included good product quality, while the weakness factor was the lack of promotion in product marketing that had not been implemented. Meanwhile, external factors that can support and hinder the growth and development of the rattan craft business in Keudee Bieng Village are opportunity factors which include potential locations that support the business and threat factors include the influence of competitors' entry. With this, external and internal factors have a significant effect on the strategy of developing rattan handicraft business in Keude Bieng Village, Lhoknga District, Aceh Besar District. The most appropriate is to use an aggressive strategy, namely a strategy that uses strength to take advantage of existing opportunities. Rattan craft business owners should carry out marketing management through digital marketing promotions and directly to all consumers, especially those in the Aceh area, so that it will expand consumer interest to buy and minimize the entry of competitors in the rattan craft business in Keudee Bieng, so that it will minimize the weaknesses that arise. exist in the industry, and can maintain existing strengths and opportunities.